Análise do preconceito generalizado no Brasil - Silva, Ana Beatriz dos Anjos (2024)
The aim of this dissertation is to identify correlations between different types of prejudice that may constitute the phenomenon of generalized prejudice. It was based on the hypothesis that there are positive correlations between the types of prejudice analyzed here (e.g. LBGTphobia, sexism, racism, fatphobia, ableism and ageism) and that these prejudices will show differences in expression depending on sociodemographic variables (e.g. age, sexual orientation, gender identity, marital status, monthly income, religion, political position, height, weight, disability, status, skin color). In order to achieve this objective, in addition to the theoretical chapters, a scoping review and an empirical, cross-sectional, quantitative study were carried out. The scoping study suggests that the main constructs related to generalized prejudice (GP) are Social Dominance Orientation and Right-wing Authoritarianism. However, some studies show that GP is associated with endo- and exogroup dynamics, although no correlation analyses have been found that associate GP with “majority” groups in society. The empirical study was carried out online, on the GoogleForms platform, with 305 participants aged over 18. The instruments were: Sociodemographic questionnaire, Scale of prejudice against sexual and gender diversity (Costa et al, 2015), Inventory of Ambivalent Sexism (Formiga et al, 2002), Scale of Revictimizing Racism (Lima et al, 2020), Scale of Antiobesity Attitudes (Obara & Alvarenga, 2016), Scale on Conceptions of disability (Leite & Lacerda, 2018), Scale of ambivalent idadism (Vieira, 2018), Defining Issues Test (Camino et al, 1996). The results show correlations between different types of prejudice. Revitimizing Racism correlates positively with both forms of Idadism and Sexism (hostile and benevolent), with prejudice against sexual and gender diversity, and with two domains of Capacitism (Metaphysical and Historical-Cultural), revealing the existence of a generalized prejudice. Moral Judgments showed a weak correlation with Hostile Sexism, with no correlation with other types of prejudice. Generalized prejudice is stronger in certain groups, especially right-wing groups. Structural Equation Modeling (SEM) explained the correlation between prejudices and, in a second analysis with Moral Judgment as a covariate, it was shown that it is related to generalized prejudice. The Post Hoc test revealed significant differences between political groups in prejudice against sexual diversity, Revitimizing Racism (higher in the Center-Right), Fatphobia (Center-Left), Ageism (Left) and Sexism (Center and Right). Capacitism showed no differences between political groups. This study contributes to the study of generalized prejudice in Brazil, with a large and homogeneous sample and explored a diversity of groups at once, being one of the few studies of its kind in the country.